Experience Spanish un mundo sin límites - Amores, María; Suárez García, José Luis; Wendel, Annie Rutter (New York McGraw-Hill Education, 2020)
Experience Spanish: Un mundo sin límites, presents vocabulary and grammar in action through culture. With emphasis on the 5C's, the Experience Spanish program delivers dynamic opportunities for communicative practice in all course delivery formats. It creates a competitive environment, it takes their learning beyond the classroom environment, and it promotes motivation and positive attitudes toward language learning" --Provided by publisher.
Keywords: Spanishh language -- Textbooks for foreign speakers -- English; Spanish language -- Grammar; Spanish language -- Spoken Spanish